(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study was motivated by the low level of students’ skills in writing response texts. The purpose of this study was to improve the response text writing skills of seventh grade students at UPTD SMP Negeri 7 Gunungsitoli through the application of the inquiry learning model. The research method used was Classroom Action Research (CAR), which was carried out in two cycles. The research subjects were seventh-grade students at UPTD SMP Negeri 7 Gunungsitoli. Research data were collected through questionnaires, observations, and written tests, then analyzed using comparative descriptive techniques by comparing learning outcomes in cycle I and cycle II. The results of the study show an increase in response writing skills. The percentage of student learning completeness increased from 45% in cycle I to 92% in cycle II. The percentage of learning effectiveness also increased from 62% in cycle I to 88% in cycle II. Thus, it can be concluded that the application of the inquiry learning model is able to improve students’ response writing skills in a good, creative, and innovative manner.